Pengaruh Media Sosial Instagram Dan Relationship Marketing Terhadap Minat Beli Konsumen Pada Era Industri 4.0 (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to determine the potential of Instagram and relationship marketing on consumer buying interest in the industrial era 4.0. The development of science and technology to date can provide convenience and assistance for humans to become entrepreneurs. In order for the business to run according to plan, the company must utilize technology well and always develop innovative ways to achieve the expected goals.This study uses a sampling technique using purposive sampling obtained a sample of 90 respondents from using the questionnaire method. The data analysis technique used in this research is multiple linear regression. The results of this study indicate that the Instagram variable has a positive and significant effect on consumer buying interest. Relationship marketing has a positive and significant effect on consumer buying interest. Together, Instagram and relationship marketing variables have a positive and significant effect on consumer buying interest.. Keywords: social media instagram, relationship marketing, custoner buying interest